Pertussis-like syndrome often not associated with Bordetella pertussis: 5-year study in a large children's hospital. Issue 10 (2nd October 2020) - Xiong, Qin; Hao, Shiying; Shen, Lei; Liu, Jian; Chen, Tingting; Zhang, Guoqin; Huang, Yu-juan
Abstract: Background: Recently, a resurgence of pertussis has been observed worldwide despite broad vaccination coverage. The purpose of this study was to identify the clinical characteristics and the aetiological agent of pertussis-like syndrome (PLS) in Eastern China. Methods: 1168 patients who were diagnosed with a suspected Bordetella pertussis in Shanghai Children's Hospital from 2013 to 2017 were included in the study. Clinical features and aetiologies were analysed. Aetiological analyses in sub-cohorts of age, seasons and years were also investigated. Results: 96.0% (1121) of the patients were less than 12 months old. 59.0% (689) of the patients were male. The Top 5 pathogens were respiratory syncytial virus (RSV; n  = 125; 10.7%), Streptococcus pneumonia (SP; n  = 109; 9.3%), Haemophilus influenzae type b (HIB; n  = 86; 7.4%), Bordetella pertussis ( B. pertussis ; n  = 84; 7.2%), and Mycoplasma pneumonia (MP; n  = 80; 6.9%), respectively. The percentage of SP in the age group of 0–3 months was significantly lower than that in other age groups. The percentage of B . pertussis in the age group of 3–6 months was significantly lower than that in the group of 6-12 months. The percentage of MP in 0-3 months' group was significantly lower than that in >12 months group. RSV peaked in winter ( n  = 52), while HIB peaked in spring ( n  = 38). Conclusion: PLS occurred most often in infants. RSV, SP, HIB, B . pertussis, and MP were the most prevalent pathogens. Since patients with B . pertussis and other pathogens have similar clinical manifestations, diagnosis of pertussis should be based on both clinical symptoms and laboratory confirmation.